Cell-of-origin DNA methylation signatures are maintained during colorectal carcinogenesis - Bormann, Felix; Rodríguez Paredes, Manuel; Lasitschka, Felix; Edelmann, Dominic; Musch, Tanja; Benner, Axel; Bergman, Yehudit; Dieter, Sebastian M.; Ball, Claudia R.; Glimm, Hanno; Linhart, Heinz G.; Lyko, Frank (Cell reports, 2018)
Colorectal adenomas are precursor lesions of colorectal cancers and represent clonal amplifications of single cells from colonic crypts. DNA methylation patterns specify cell-type identity during cellular differentiation and, therefore, provide opportunities for the molecular analysis of tumors. We have now analyzed DNA methylation patterns in colorectal adenomas and identified three biologically defined subclasses that describe different intestinal crypt differentiation stages. Importantly, colorectal carcinomas could be classified into the same methylation subtypes, reflecting their shared cell types of origin with adenomas. Further data analysis also revealed significantly reduced overall survival for one of the subtypes. Our results provide a concept for understanding the methylation patterns observed in colorectal cancer and provide opportunities for tumor subclassification and patient stratification.